The Relationship between Diet Compliance and Physical Activity with Blood Sugar Levels in Patients with Type II Diabetes Mellitus in the Work Area of the Pasundan Health Center - Natalia Fitriani; Joko Sapto Pramono; Kurniati Dwi Utami (Formosa Journal of Science and Technology, 2023)
Diabetes Mellitus is a disorder of the metabolic system with increased blood sugar levels (hyperglycemia), caused by the inability of the pancreas to produce insulin or lack of insulin sensitivity. Management of DM has four pillars, namely education, diet therapy, physical activity, and drug therapy. The purpose of this study was to determine the relationship between dietary adherence and physical activity with blood sugar levels in patients with Type II Diabetes Mellitus in the working area of ​​the Pasundan Health Center. This type of research is analytic observational with cross sectional design. Sampling using consecutive sampling technique and a total sample of 40 people. The data analysis used is the Spearman Rank Test. The results of the study showed a relationship between dietary compliance and GDS levels (p = 0.000) and there was a relationship between physical activity and GDS levels (p = 0.026).